Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula - Kim, Wongun; Kim, Junggon; Lee, Hodan; Rédei, Dávid; Jung, Sunghoon (Zootaxa, 2017)
The species of the genus Elasmostethus Fieber, 1860 (Hemiptera: Heteroptera: Acanthosomatidae) occurring in the Korean Peninsula are reviewed. Six species are recognized; the occurrence of four previously recorded species, including E. brevis Lindberg, 1934, E. humeralis Jakovlev, 1883, E. interstinctus (Linnaeus, 1758), and E. nubilus (Dallas, 1851) is confirmed; two species, E. rotundus Yamamoto, 2003, and E. yunnanus Hsiao & Liu, 1977, are recorded for the first time from Korea. The record of E. kansuensis Hsiao & Liu, 1977, is based on misidentification of E. yunnanus, the former species is deleted from the Korean fauna. Photographs of habitus and genital segments of all the recognized Korean species are included, diagnoses and a key to the Korean species are provided.